Satellite Tracking Sea Turtles: Opportunities and Challenges to Address Key Questions - Hays, Graeme C.; Hawkes, Lucy A. (Frontiers in Marine Science, 2018)
Over 25 years ago the first satellite tracking studies of sea turtles were published. The technology and attachment methods have now come of age with long-term tracks over a year being commonplace and the ability to relay high resolution GPS locations via the Argos satellite system along with behavioural (e.g. diving and activity) and environmental (e.g. temperature) data. Early studies focused on breeding females because they come ashore to nest, allowing individuals to be restrained relatively easily for tag attachment. However, today the development of methods for the capture of turtles at sea are increasingly allowing studies on both adult male turtles as well as immature turtles as small as 11cm carapace length. Here we review the extent of work after many thousands of individual turtles have been tracked. We consider the state-of-the-art equipment for satellite tracking turtles and how this technology is being used to tackle key questions. We highlight some of the emerging opportunities arising from improved spatial resolution of tracking, increased robustness and miniaturisation of tags as well as increasing availability of environmental data. We highlight the huge potential for big-data studies to make use of the thousands of tracks that exist, although we discuss the long-standing challenges surrounding data accessibility.